2018
DOI: 10.1152/ajpheart.00414.2017
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate supplementation in cardiovascular health: an ergogenic aid or exercise therapeutic?

Abstract: Oral consumption of inorganic nitrate, which is abundant in green leafy vegetables and roots, has been shown to increase circulating plasma nitrite concentration, which can be converted to nitric oxide in low oxygen conditions. The associated beneficial physiological effects include a reduction in blood pressure, modification of platelet aggregation, and increases in limb blood flow. There have been numerous studies of nitrate supplementation in healthy recreational and competitive athletes; however, the ergog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 248 publications
1
17
0
Order By: Relevance
“…Herein, we report that oral inorganic nitrate supplementation resulted in a greater increase in Q in two (out of three) stages of discontinuous incremental exercise. These differences were seen specifically during the higher intensity workloads, which is in line with previous work indicating the effects of nitrate supplementation are more pronounced in low oxygen conditions [13]. This finding is in agreement with an earlier study by Zamani et al in which patients with HFpEF demonstrated increases in Q (measured with echocardiography) following a single acute dose of 12.9mmol inorganic nitrate [17].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Herein, we report that oral inorganic nitrate supplementation resulted in a greater increase in Q in two (out of three) stages of discontinuous incremental exercise. These differences were seen specifically during the higher intensity workloads, which is in line with previous work indicating the effects of nitrate supplementation are more pronounced in low oxygen conditions [13]. This finding is in agreement with an earlier study by Zamani et al in which patients with HFpEF demonstrated increases in Q (measured with echocardiography) following a single acute dose of 12.9mmol inorganic nitrate [17].…”
Section: Discussionsupporting
confidence: 92%
“…Inorganic nitrate supplementation is an established intervention for increasing NO bioavailability in both healthy and diseased populations [11,12]. While previous studies have demonstrated improvements in exercise performance and vascular outcomes in diverse clinical cohorts, the majority of studies in HFrEF have indicated that supplementation has a minimal effect [13][14][15][16] However, evidence in HFpEF suggests the potential for nitrate (and nitrite) supplementation to improve systemic vascular resistance (SVR) and cardiac output (CO) [10,17]. To our knowledge, no study to date has examined the effects of supplementation on measures of cardiac function during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…As an ammonia‐oxidizing bacteria (AOB), Nitrosomonas eutropha utilizes ammonia from sweat to generate nitrite and nitric oxide. Studies have shown that nitrite and nitric oxide are associated with beneficial physiological effects including vasodilation, anti‐inflammatory properties, improved wound healing, and reduced blood pressure . In pre‐clinical studies, Nitrosomonas eutropha led to a reduction in pathogenic bacteria on the skin (eg, Propionibacterium acnes ), as well as improved skin healing .…”
Section: Introductionmentioning
confidence: 99%
“…A beneficial effect also appears more likely following chronic dosing regimens in less conditioned individuals (including those with cardiovascular impairments) employing higher intensity activities which utilize fast twitch muscle fibres (Woessner et al . ).…”
Section: Role Of Skeletal Muscle Nitrogen Oxides In Exercise Performancementioning
confidence: 97%
“…In healthy human studies the results are mixed with meta-analyses reporting overall no benefit for maximal graded exercise and time trial performance testing, but likely a benefit in time to exhaustion tests. A beneficial effect also appears more likely following chronic dosing regimens in less conditioned individuals (including those with cardiovascular impairments) employing higher Perspectives J Physiol 597.23 intensity activities which utilize fast twitch muscle fibres (Woessner et al 2018).…”
Section: Role Of Skeletal Muscle Nitrogen Oxides In Exercise Performancementioning
confidence: 99%